Coding reliability and agreement of international classification of disease, 10th revision (ICD-10) codes in emergency department data - Peng, Mingkai; Eastwood, Cathy; Boxill, Alicia; Jolley, Rachel Joy; Rutherford, Laura; Carlson, Karen; Dean, Stafford; Quan, Hude (International Journal of Population Data Science, 2018)
Introduction: Administrative health data from the emergency department (ED) play important roles in understanding health needs of the public and reasons for health care resource use. International Classification of Disease (ICD) diagnostic codes have been widely used for code reasons of clinical encounters for administrative purposes in EDs. Objective: The purpose of the study is to examine the coding agreement and reliability of ICD diagnosis codes in ED through auditing the routinely collected data. Methods: We randomly sampled 1 percent of records (n=1636) between October and December from 11 emergency departments in Alberta, Canada. Auditors were employed to review the same chart and independently assign main diagnosis codes. We assessed coding agreement and reliability through comparison of codes assigned by auditors and hospital coders using the proportion of agreement and Cohen’s kappa. Error analysis was conducted to review diagnosis codes with disagreement and categorized them into six groups. Results: Overall, the agreement was 86.5% and 82.2% at 3 and 4 digits levels respectively, and reliability was 0.86 and 0.82 respectively. Variation of agreement and reliability were identified across different emergency departments. The major two categories of coding discrepancy were the use of different codes for the same condition (23.6%) and the use of codes at different levels of specificity (20.9%). Conclusions: Diagnosis codes in emergency department show high agreement and reliability. More strict coding guidelines regarding the use of unspecified codes are needed to enhance coding consistency.